Involvement of microenvironment factors in the PTHrP effect on the aggressive behavior of colorectal cancer cells - Novoa Díaz, María Belén (2019)
PTHrP is a factor from the tumor and its microenvironment that has been associated with the aggressiveness of different types of cancer. Colorectal cancer (CRC) is a heterogeneous disease where microenvironment and tumor factors act together leading to the progression of the tumor towards advanced stages. Previously, we observed that in the cell line HCT116 derived from human CRC, the treatment with exogenous PTHrP stimulates its transcription and also modulates the expression of markers associated with aggressive behavior such as E-Cadherin, FAK, Met and CD44. In addition PTHrP activates mitogenic pathways in HMEC-1 endothelial cells. To understand the PTHrP role in tumor progression through its influence on microenvironment cells, in this work we first evaluated in HMEC cells the effects of PTHrP in the regulation of cytokines expression and we observed by Western blot analysis that the treatment with the hormone for 1 and 16 h increases protein levels of TGF-β, which is a protumoral factor known to be closely linked to PTHrP. Then we evaluate the effect of the conditioned medium (CM) from the HMEC-1 cells treated with PTHrP on the intestinal tumor cells HCT116. According with our previous results regarding to PTHrP direct action on HCT116 cells, the CM also induces an increase in the protein expression of FAK and CD44 in a time-dependent manner, and decreases the protein level of E-cadherin but at shorter times respect to the direct action of PTHrP. Previously we found that PTHrP increases the protein levels of Met in HCT116 cells and herein we observed by CM treatment the same effect but at longer times of exposure. The results of this work allow us to postulate a mechanism based in the action of PTHrP on tumor niche cells leading to the subsequent release of factors to the environment that could contribute to its protumoral effect.